2021
DOI: 10.1155/2021/3081549
|View full text |Cite|
|
Sign up to set email alerts
|

Application Analysis Based on Big Data Technology in Stroke Rehabilitation Nursing

Abstract: According to the statistical analysis, the incidence of stroke disease has gradually increased, particularly in recent years, which poses a huge threat to the safety of human life. Due to the advancement in science and technology specifically big data and sensors, a new research dome known as data mining technology has been introduced, which has the potential value from the perspective of large amount of data analysis. Information has become a new trend of science and technology, and data mining has been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This study found that the three-level stroke RIMS not only improved the efficiency of daily stroke management but also improved the satisfaction and clinical outcomes of stroke patients. This observation was consistent with the findings of Xu et al (2021) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that the three-level stroke RIMS not only improved the efficiency of daily stroke management but also improved the satisfaction and clinical outcomes of stroke patients. This observation was consistent with the findings of Xu et al (2021) .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that clinical pathways can significantly reduce the length of hospital stay and the cost of stroke care for patients ( Deng et al, 2014 ; Pilato et al, 2021 ). The three-level rehabilitation, also known as the regional clinical pathway ( Fujino et al, 2014 ), is a seamless integration of the acute stroke clinical pathway (Stroke Unit), the convalescent clinical pathway, and the chronic clinical pathway ( Xu et al, 2021 ). This facilitates the discharge of stroke patients with significant burdens and allows the tertiary hospitals to accept patients with severe conditions ( Van der Cruyssen et al, 2015 ) and refer discharged patients to the next level of the hospital for appropriate treatment according to their condition, thus saving treatment costs without reducing the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%